A fish tale - Bravo, Becky; Dela Cruz, Daniel (Quezon City : CANVAS, 2014)
Koi lives underwater with his Grandfather Agu but looks different from the rest of the sea creatures. One day, Koi swam near fishing boats. He found himself in the care of human beings that looked like him, but Koi chose to swim back home.
Winner of CANVAS' Romeo Forbes Children's Story Writing Competition
Keywords: Children's stories; Electronic Books